STRENGTH CALCULATION OF NORMAL SECTION ECCENTRICALLY COMPRESSED REINFORCED CONCRETE COLUMN USING DEFORMATION MODEL (Збірник наукових праць Галузеве машинобудування будівництво, 2017)
Example of calculating normal section strength eccentrically compressed reinforced concrete column is presented in the work. The author used in the calculation of deformation models DBN B.2.6 - 98: 2009, which is based on polynomial diagram of concrete which contains clarified values of coefficients. Values of coefficients obtained through the introduction of boundary conditions, which are crucial for the characteristic common points of approximations diagrams physical condition of concrete. The notion extreme of strength criterion applied in order for getting limit values of concrete deformation. The case is considered when the concentrated force applied from eccentricity, which coincides with one symmetry axes of section. Method of calculating strength of normal section eccentrically compressed reinforced concrete elements are pressed and can be used in engineering calculations. Keywords: strength, eccentric compression, column, concrete, extreme criterion concrete diagram.